Anonymous living liver donor perspectives on the role of family in their donation experience. Issue 3 (20th December 2021) - Humar, Sapna; Jung, Judy; Krause, Sandra; Selzner, Nazia; Abbey, Susan
Abstract: Anonymous living organ donation is an understudied but rapidly expanding sector in organ transplantation, in which donors choose to donate anonymously to a recipient in need. The family members and close support network of living donors often play a crucial role in the donation process, and their influence likely has a large impact on the decision to donate as well as the donor's physical and psychosocial state. However, there is limited data examining the impact donor families have on the anonymous donor, and in turn, the impact donation has on donors' families. To assess this, we analyzed a semi‐structured qualitative interview on living donor experiences with 26 anonymous living liver donors for common themes concerning donor families. Responses surrounding donor families were grouped into three major categories: (1) family reactions to donation, ranging from (a) pride/support, (b) fear/worry, and (c) jealousy/anger; (2) the impact of donation on donor‐family relationships, including (a) positive impacts, (b) negative impacts, (c) a positive ripple effect; (3) gaps in institutional support for donor families. This study provides unique information on anonymous living liver donor perceptions related to their families and will help improve existing programs to accommodate donor family needs and cater to donor relationships.